Mehr als Opfer: Kriegskinder und ihr Überleben in den Kinderheimen im besetzten Belarus = More than victims : war children and their survival in the children's homes in occupied Belarus - Saal, Yuliya von (Jahrbücher für Geschichte Osteuropas, 2020)
In the memorial landscape of post-Soviet states, the image of the defenseless child, recalling the suffering of the civilian population in the Great Patriotic War, is increasingly common. This visual communication makes minors the focus of memory as a separate community of experience, thereby conveying a historical narrative that exclusively centers on passive victims. Children were above all innocent victims, but also actors with their own abilities, resources, and coping potential. The article illustrates this based on the example of orphaned children in occupied Belarus. It sheds light on the functioning of the orphanage system under German occupation and classifies the individual experiences of the children, their everyday life, and their spaces of action using the example of the children’s homes in the Minsk region. The article shows that children’s homes were not just places of misery, but also of survival. For Jewish children in particular, they often became the last refuge, albeit one ridden with danger.
Gesehen am 18.02.2026